Politicaltainment in the Compartment Politic of Republika - Wahyuni Choiriyati (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
Industrial era of mass media is signed by the change of the climate of information freedom, soon after the ruin of 'New Era'; mass media underwent a lot of changing. The most significant influence for mass media industrial change is the change of the format and contain of the political news. Through the Politicaltainment research, the researcher wants to examine how the political information does is served pragmatically. This research is being used setting agenda strategy to examine the main issues which are constructed by political compartment of Republika daily newspaper. Qualitative approach is used to examine the reflection of press work deeply through political compartment of Republika daily newspaper. The climate of the industry, actually, creates the format of the news as the part of the changing rate of rupiah value, takes place comodification practice of political news in this kind of situation. Basically, politic news is an effort to build powerful social realization and political knowledge. Keywords: comodification,agendasetting,politicalcompartment.